Angiogenic Factor Estimation as a Warning Sign of Preeclampsia-Related Peripartum Morbidity Among Hospitalized Patients. Issue 4 (April 2019) - Lopes Perdigao, Joana; Chinthala, Sireesha; Mueller, Ariel; Minhas, Ruby; Ramadan, Hadi; Nasim, Rabab; Naseem, Heba; Young, Danielle; Shahul, Sana; Chan, Siaw Li; Yeo, Kiang-Teck J.; Rana, Sarosh
Abstract : Preeclampsia-related morbidity and mortality is rising predominantly because of delayed identification of patients at risk for preeclampsia with severe features and associated complications. This study explored the association between angiogenic markers (sFlt1 [soluble fms-like tyrosine kinase-1]) and PlGF [placental growth factor]) and preeclampsia-related peripartum complications. Normotensive women or those with hypertensive disorders of pregnancy were enrolled. Blood samples were collected within 96 hours before delivery, and angiogenic markers were measured on an automated platform. Our study included 681 women, 375 of which had hypertensive disorders. Of these, 127 (33.9%) had severe preeclampsia, and 71.4% were black. Compared with normotensive women, women with severe preeclampsia had higher levels of sFlt1 (9372.5 versus 2857.0 pg/mL; P <0.0001), lower PlGF (51.0 versus 212.0 pg/mL; P <0.0001), and a high sFlt1/PlGF (212.0 versus 14.0; all P <0.0001). A similar trend in sFlt1, PlGF, and sFlt1/PlGF was found in those women with complications secondary to preeclampsia (all P <0.001). The highest tertile of sFlt1/PlGF was strongly associated with severe preeclampsia in a multivariable analysis. Among patients with a hypertensive disorder of pregnancy, 340 (90.7%) developed postpartum hypertension, of which 50.4% had mild, and 40.3% had severe postpartum hypertension. The sFlt1/PlGF ratio was significantly higher for severe and mild postpartum hypertension compared with women with normal postpartum blood pressures (73.5, 46.0, and 13.0, respectively; P values<0.0001). Furthermore, the highest tertile of antepartum sFlt1/PlGF was associated with postpartum hypertension ( P =0.004). This study demonstrates a significant association between an abnormal angiogenic profile before delivery and severe preeclampsia and peripartum complications. Abstract : Supplemental Digital Content is available in the text.